Digital Measuring Instruments for Height and Weight with Microcontroller-Based Sound Output - Adi Chandranata; Roza Susanti; Ade Hakimi Putri (Publikasi Indonesia, 2024)
Height and weight measuring devices simultaneously provide ideal weight information that will be handy for users. This study aims to provide an instrument that can be used as a measuring instrument for height and weight and whether or not a person's body is ideal. Therefore, in research, measuring instruments that can simultaneously measure height and weight and provide ideal information or not measured weight. This measuring instrument uses Arduino Uno as its brain, ultrasonic sensors to measure height, and strain gauge/load cell sensors to measure weight. Arduino processes data from both sensors to get the ideal body weight (BBI). The height, weight, and ideal body criteria values will be displayed on the LCD. Furthermore, the speaker will issue sound information regarding the condition of body weight, namely ideal, fat, or thin. Based on the testing and data analysis results, the average error percentage value in height measurement is 0.45%, and in weight measurement is 1.65%. At the same time, the success rate of the appearance of voice information is 99%.